Percepción de la salud mental de las trabajadoras sexuales transgénero de una localidad de la ciudad de Bogotá (2023)
Transgender sex workers are a population that has been discriminated against and segregated in society; factors that can cause damage to different aspects of your mental health. In Colombia there has been a lack of information regarding the mental health of sex workers, which have been characterized by not having enough data to generate and implement active promotion strategies by nursing professionals and thus respond assertively to their needs in the face of the perception of mental health, according to the risk factors that affect them, and thus know if there are self-care activities, where nursing is fulfilling its strategic role in primary health care for the care of sex workers. Objective: To describe transgender sex workers' perception of mental health. Methodology: Study of qualitative approach of phenomenological descriptive character, with transgender sex workers to whom a sociodemographic characterization sheet was applied for the subsequent realization of a semi-structured interview. Results: Through the data obtained through the information provided by transgender sex workers, it was identified that the concept of mental health for this population is related to emotions and a state of balance, which can be altered by different internal and external factors, such as discrimination, stigmatization, social relationships and the processes of their transition; what makes it necessary, as they express it, to create interventions and programs according to their needs at the mental health level; in addition to social regulations that manage to generate protection for the population. Conclusions: With this research, it was possible to determine the perception of mental health by transgender women sex workers in the city of Bogotá, identifying and characterizing the areas inhabited by the interviewees, in addition to recognizing the concept of mental health on the part of the women. themselves and the factors that influence the mental health of transgender women sex workers were analyzed